Attracting Viewers through Advertisement by Using Code Mixing: A Sociolinguistics Study - Herman, Herman; Thao, Nguyen Van; Purba, Ridwin; Simanjuntak, Novi Sri Ulina (CV. Creative Tugu Pena, 2022)
The artcile aims to clarify what types of code mixes are used in TV advertisements and why code mixing is used because a trend or style of speech in society, particularly among young people has evolved in the phenomenon of mixing code and changing code. Bilingualism always involves the use of code mixing in the daily conversation of people. This research was carried out with a qualitative description. The research used transcript by note as an instrument, for the purpose of this research. Note that the video transcription method was used. The information is 30 ads. Data from this research were all published on Tuesday, 1 June 2021, through Saturday 6 June 2021, by the 30 television ads selected by the researchers. The result is a compatible lexicalization and insertion which appears as types of code mixing in the advertising. and 4 reasons were found, namely talking on a specific subject, interjection, intention to clarify the content of the speech and group identity expression. Keywords: Sociolinguistic, Code Mixing, Advertisement Analysis